Positive electrode material, positive electrode plate, secondary battery and electronic device
By regulating the particle size distribution of lithium manganese iron phosphate and adding carbon elements, the shortcomings in its energy density and performance are solved, and better processing, dynamics and cycling performance are achieved.
Patent Information
- Application Number
- CN202411570308.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Lithium manganese iron phosphate batteries have problems such as low energy density, poor kinetic performance and cycling performance.
By regulating the particle size distribution of lithium manganese iron phosphate, it contains particles with a smaller particle size, a medium particle size and a larger particle size, and adding an appropriate amount of carbon elements to it to improve its electronic conductivity.
The processing performance, dynamic performance and cycling performance of the positive electrode material are improved, and the overall performance of the secondary battery is improved.
Smart Images

Figure CN119481040A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a positive electrode material, a positive electrode sheet, a secondary battery and an electronic device. Background Art
[0002] In order to solve the severe problems of global energy crisis, environmental pollution, climate change, low-carbon economy, etc., the research and development and application of power sources in electric vehicles, large-scale power sources and energy storage fields have become inevitable. As an important component of them, lithium iron phosphate batteries have the advantages of long life, safety and low cost, but lithium iron phosphate has the problem of low energy density.
[0003] Adding a certain proportion of Mn into lithium iron phosphate increases its average voltage and energy density. However, lithium manganese iron phosphate has the Jan-Taylor effect, and its kinetic and cycle performances are poor. Summary of the invention
[0004] The purpose of this application is to provide a positive electrode material, a positive electrode sheet, a secondary battery and an electronic device to improve the processing performance, dynamic performance and cycle performance of the positive electrode material. The specific technical solution is as follows:
[0005] The first aspect of the present application provides a positive electrode material, the positive electrode material includes lithium manganese iron phosphate, in the scanning electron microscope image of lithium manganese iron phosphate with a magnification of 10000 times and within a range of 10μm×8μm, the total number of primary particles of lithium manganese iron phosphate is N, the number of primary particles of lithium manganese iron phosphate with a particle size of Φ1nm is N1, and the number of primary particles of lithium manganese iron phosphate with a particle size of Φ2nm is N2, N≥200; 50<Φ1≤100, 10%≤N1 / N≤30%; 100<Φ2≤150, 15%≤N2 / N≤35%. The positive electrode material meets the above characteristics, can improve the processing performance, dynamic performance and cycle performance of the positive electrode material, and the application of the above positive electrode material in a secondary battery can make the secondary battery have better processing performance, dynamic performance and cycle performance.
[0006] In one or more embodiments of the present application, the number of primary particles of lithium iron manganese phosphate with a particle size of Φ3 nm is N3, Φ3≤50, 0≤N3 / N≤10%. When the ratio of the number N3 of primary particles of lithium iron manganese phosphate with a particle size Φ3 satisfying Φ3≤50 to the total number N of primary particles of lithium iron manganese phosphate is within the scope of the present application, the lithium iron manganese phosphate satisfies the above particle size distribution, and the particles with smaller particle sizes in the lithium iron manganese phosphate can further improve the kinetic properties of the positive electrode material, such as rate performance or low-temperature discharge performance, and further reduce the attenuation of the kinetic properties of the positive electrode material during the cycle.
[0007] In one or more embodiments of the present application, the number of primary particles of lithium iron manganese phosphate with a particle size of Φ4 nm is N4, 150<Φ4≤250, 20%≤N4 / N≤40%. When the ratio of the number N4 of primary particles of lithium iron manganese phosphate with a particle size Φ4 satisfying 150<Φ4≤250 to the total number N of primary particles of lithium iron manganese phosphate is within the scope of the present application, the lithium iron manganese phosphate satisfies the above particle size distribution, and the lithium iron manganese phosphate has a certain number of particles with medium particle size and larger particle size, which can further improve the processing performance of the positive electrode material, for example, increase the compaction density of the positive electrode material.
[0008] In one or more embodiments of the present application, the number of primary particles of lithium iron manganese phosphate with a particle size of Φ5 nm is N5, 250<Φ5≤350, 5%≤N5 / N≤15%. When the ratio of the number N5 of primary particles of lithium iron manganese phosphate with a particle size Φ5 satisfying 250<Φ5≤350 to the total number N of primary particles of lithium iron manganese phosphate is within the scope of the present application, the lithium iron manganese phosphate satisfies the above particle size distribution, and the lithium iron manganese phosphate has a certain number of particles with medium particle size and larger particle size, which can further improve the processing performance of the positive electrode material, for example, increase the compaction density of the positive electrode material.
[0009] In one or more embodiments of the present application, the number of primary particles of lithium iron manganese phosphate with a particle size of Φ6 nm is N6, 350<Φ6≤500, 1%≤N6 / N≤5%. When the ratio of the number N6 of primary particles of lithium iron manganese phosphate with a particle size Φ6 satisfying 350<Φ6≤500 to the total number N of primary particles of lithium iron manganese phosphate is within the scope of the present application, the lithium iron manganese phosphate satisfies the above particle size distribution, and the lithium iron manganese phosphate has a certain number of particles with larger particle sizes, which can further improve the processing performance of the positive electrode material, for example, increase the compaction density of the positive electrode material.
[0010] In one or more embodiments of the present application, the number of primary particles of lithium iron manganese phosphate with a particle size of Φ7 nm is N7, Φ7>500, 0≤N7 / N≤5%. When the ratio of the number N7 of primary particles of lithium iron manganese phosphate with a particle size Φ7 satisfying Φ7>500 to the total number N of primary particles of lithium iron manganese phosphate is within the scope of the present application, the lithium iron manganese phosphate satisfies the above particle size distribution, and the lithium iron manganese phosphate has a certain number of particles with larger particle sizes, which can further improve the processing performance of the positive electrode material, for example, increase the compaction density of the positive electrode material.
[0011] In one or more embodiments of the present application, the average particle size of lithium manganese iron phosphate is D nm, 50≤D≤200. By regulating the average particle size of lithium manganese iron phosphate within the scope of the present application, lithium manganese iron phosphate includes particles with smaller particle sizes, and also includes particles with medium particle sizes and larger particle sizes. The particles with smaller particle sizes in lithium manganese iron phosphate can improve the kinetic properties of the positive electrode material, such as rate performance or low-temperature discharge performance, and effectively reduce the attenuation of the kinetic properties of the positive electrode material during the cycle. In addition, lithium manganese iron phosphate has a certain number of particles with medium particle sizes and larger particle sizes, which can improve the processing properties of the positive electrode material, such as increasing the compaction density of the positive electrode material.
[0012] In one or more embodiments of the present application, based on the mass of lithium iron manganese phosphate, the mass percentage of carbon in the lithium iron manganese phosphate is Wc%, 1.0≤Wc≤2.5, preferably, 1.3≤Wc≤2.0; more preferably, 1.5≤Wc≤1.8. By regulating the mass percentage of carbon in the lithium iron manganese phosphate within the scope of the present application, the electronic conductivity of the lithium iron manganese phosphate can be further improved, thereby further improving the kinetic performance and cycle performance of the positive electrode material.
[0013] In one or more embodiments of the present application, the specific surface area of lithium manganese iron phosphate is SSAm 2 / g, 12≤SSA≤35; preferably, 14≤SSA≤20. By regulating the specific surface area of lithium manganese iron phosphate within the scope of this application, lithium manganese iron phosphate has a suitable specific surface area, lithium manganese iron phosphate has a suitable particle size distribution, lithium manganese iron phosphate includes particles with smaller particle sizes, and also includes particles with medium particle sizes and larger particle sizes. The particles with smaller particle sizes in lithium manganese iron phosphate can improve the kinetic properties of the positive electrode material, such as rate performance or low-temperature discharge performance, and effectively reduce the attenuation of the kinetic properties of the positive electrode material during the cycle. In addition, lithium manganese iron phosphate has a certain number of particles with medium particle sizes and larger particle sizes, which can improve the processing performance of the positive electrode material, such as increasing the compaction density of the positive electrode material.
[0014] In one or more embodiments of the present application, the powder resistivity of lithium iron manganese phosphate is ρΩ·cm, 10≤ρ≤300, preferably, 10≤ρ≤100. By regulating the powder resistivity of lithium iron manganese phosphate within the scope of the present application, the powder resistivity of lithium iron manganese phosphate is small, the electronic conductivity of lithium iron manganese phosphate is good, and the kinetic performance and cycle performance of the positive electrode material can be further improved.
[0015] In one or more embodiments of the present application, the chemical formula of lithium manganese iron phosphate is Li x Mn y Fe 1-y-z M zPO4, 1.0≤x≤1.1, 0.5≤y≤0.8, 0≤z≤0.02, M includes at least one of Mg, Ti, Nb, V, Ni or Co. The above-mentioned lithium manganese iron phosphate is selected, and the lithium manganese iron phosphate has a higher energy density. At the same time, the lithium manganese iron phosphate satisfies the above-mentioned particle size distribution. The lithium manganese iron phosphate includes particles with smaller particle sizes, and also includes particles with medium particle sizes and larger particle sizes, which can make the positive electrode material have better processing performance, dynamic performance and cycle performance. The above-mentioned positive electrode material is used in a secondary battery, which can make the secondary battery have better processing performance, dynamic performance, cycle performance and higher energy density.
[0016] The second aspect of the present application provides a positive electrode plate, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, the positive electrode material layer includes the positive electrode material in any of the above embodiments. Therefore, applying the positive electrode plate to a secondary battery can enable the secondary battery to have better processing performance, dynamic performance and cycle performance.
[0017] The third aspect of the present application provides a secondary battery, the secondary battery comprising the positive electrode sheet in any of the above embodiments. Therefore, the secondary battery provided by the present application has good processing performance, dynamic performance and cycle performance.
[0018] The fourth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good processing performance, dynamic performance and cycle performance.
[0019] Beneficial effects of this application:
[0020] The present application provides a positive electrode material, a positive electrode sheet, a secondary battery and an electronic device, wherein the positive electrode material includes lithium manganese iron phosphate, and in a scanning electron microscope image of lithium manganese iron phosphate with a magnification of 10,000 times and within a range of 10 μm×8 μm, the total number of primary particles of lithium manganese iron phosphate is N, the number of primary particles of lithium manganese iron phosphate with a particle size of Φ1 nm is N1, and the number of primary particles of lithium manganese iron phosphate with a particle size of Φ2 nm is N2, N≥200; 50<Φ1≤100, 10%≤N1 / N≤30%; 100<Φ2≤150, 15%≤N2 / N≤35%. The positive electrode material meets the above characteristics and can improve the processing performance, dynamic performance and cycle performance of the positive electrode material.
[0021] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0023] Figure 1 This is a scanning electron microscope image of the positive electrode material of Example 1-1 of the present application. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0025] It should be noted that in the following content, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0026] A first aspect of the present application provides a positive electrode material, the positive electrode material comprising lithium manganese iron phosphate. In a scanning electron microscope image of the lithium manganese iron phosphate with a magnification of 10,000 times and within a range of 10 μm×8 μm, the total number of primary particles of the lithium manganese iron phosphate is N, the number of primary particles of the lithium manganese iron phosphate with a particle size of Φ1 nm is N1, and the number of primary particles of the lithium manganese iron phosphate with a particle size of Φ2 nm is N2, N≥200; 50<Φ1≤100, 10%≤N1 / N≤30%; 100<Φ2≤150, 15%≤N2 / N≤35%. For example, the value of N can be 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 500, 700, 900, 1000, 1300, 1500, 1700, 1900, 2000, or a range consisting of any two of the above values; Φ1 can be 51, 53, 55, 57, 59, 60, 63, 65, 67, 70, 73, 75, 77, 80, 83, 85, 87, 90, 93, 95, 97, 100, or a range consisting of any two of the above values; N1 / N can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30% or a range consisting of any two of the above values; Φ2 can be 101, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150 or a range consisting of any two of the above values; N2 / N can be 15%, 17%, 19%, 20%, 21%, 23%, 25%, 27%, 29%, 30%, 31%, 33%, 35% or a range consisting of any two of the above values.
[0027] The inventors have found that the positive electrode material includes lithium iron manganese phosphate. When the ratio of the number of primary particles N1 of lithium iron manganese phosphate with a particle size Φ1 that satisfies 50<Φ1≤100 to the total number of primary particles N of lithium iron manganese phosphate, and the ratio of the number of primary particles N2 of lithium iron manganese phosphate with a particle size Φ2 that satisfies 100<Φ2≤150 to the total number of primary particles N of lithium iron manganese phosphate is within the scope of this application, lithium iron manganese phosphate satisfies the above-mentioned particle size distribution, and the particles with smaller particle sizes in lithium iron manganese phosphate can improve the kinetic properties of the positive electrode material, such as rate performance or low-temperature discharge performance, and effectively reduce the attenuation of the kinetic properties of the positive electrode material during the cycle. In addition, lithium iron manganese phosphate has a certain number of particles with medium particle sizes and larger particle sizes, which can improve the processing properties of the positive electrode material, such as increasing the compaction density of the positive electrode material. Thus, the positive electrode material satisfies the above-mentioned characteristics, can improve the processing properties, kinetic properties and cycle performance of the positive electrode material, and the above-mentioned positive electrode material is applied to the secondary battery, which can make the secondary battery have better processing properties, kinetic properties and cycle performance.
[0028] In one or more embodiments of the present application, the positive electrode material includes lithium iron manganese phosphate. In a scanning electron microscope image of lithium iron manganese phosphate with a magnification of 10,000 times and a range of 10 μm×8 μm, the total number of primary particles of lithium iron manganese phosphate is N, the number of primary particles of lithium iron manganese phosphate with a particle size of Φ1 nm is N1, and the number of primary particles of lithium iron manganese phosphate with a particle size of Φ2 nm is N2, 200≤N≤2000; 50<Φ1≤100, 10%≤N1 / N≤30%; 100<Φ2≤150, 15%≤N2 / N≤35%.
[0029] In one or more embodiments of the present application, the number of primary particles of lithium manganese iron phosphate with a particle size of Φ3 nm is N3, Φ3≤50, 0≤N3 / N≤10%. For example, Φ3 can be 1, 3, 5, 7, 9, 10, 11, 13, 15, 17, 19, 20, 21, 23, 25, 27, 29, 30, 31, 33, 35, 37, 39, 40, 41, 43, 45, 47, 49, 50 or a range consisting of any two of the above values; N3 / N can be 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of the above values. When the ratio of the number N3 of primary particles of lithium manganese iron phosphate with a particle size Φ3 satisfying Φ3≤50 to the total number N of primary particles of lithium manganese iron phosphate is within the scope of the present application, the lithium manganese iron phosphate satisfies the above-mentioned particle size distribution, and the particles with smaller particle sizes in the lithium manganese iron phosphate can further improve the kinetic properties of the positive electrode material, such as rate performance or low-temperature discharge performance, while further reducing the attenuation of the kinetic properties of the positive electrode material during the cycle.
[0030] In one or more embodiments of the present application, the number of primary particles of lithium iron manganese phosphate with a particle size of Φ4 nm is N4, 150<Φ4≤250, 20%≤N4 / N≤40%. Exemplarily, Φ4 can be 151, 155, 160, 165, 170, 175, 180, 185, 190, 195, 200, 205, 210, 215, 220, 225, 230, 235, 240, 245, 250 or a range consisting of any two of the above values; N4 / N can be 20%, 21%, 23%, 25%, 27%, 29%, 30%, 31%, 33%, 35%, 37%, 39%, 40% or a range consisting of any two of the above values. When the ratio of the number N4 of primary particles of lithium iron phosphate with a particle size Φ4 satisfying 150<Φ4≤250 to the total number N of primary particles of lithium iron phosphate is within the scope of this application, the lithium iron phosphate satisfies the above-mentioned particle size distribution, and the lithium iron phosphate has a certain number of particles with medium particle size and larger particle size, which can further improve the processing performance of the positive electrode material, such as increasing the compaction density of the positive electrode material.
[0031] In one or more embodiments of the present application, the number of primary particles of lithium iron manganese phosphate with a particle size of Φ5nm is N5, 250<Φ5≤350, 5%≤N5 / N≤15%. Exemplarily, Φ5 can be 251, 255, 260, 265, 270, 275, 280, 285, 290, 295, 300, 305, 310, 315, 320, 325, 330, 335, 340, 345, 350 or a range consisting of any two of the above values; N5 / N can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or a range consisting of any two of the above values. When the ratio of the number N5 of primary particles of lithium iron phosphate with a particle size Φ5 satisfying 250<Φ5≤350 to the total number N of primary particles of lithium iron phosphate is within the scope of this application, the lithium iron phosphate satisfies the above-mentioned particle size distribution, and the lithium iron phosphate has a certain number of particles with medium particle size and larger particle size, which can further improve the processing performance of the positive electrode material, such as increasing the compaction density of the positive electrode material.
[0032] In one or more embodiments of the present application, the number of primary particles of lithium manganese iron phosphate with a particle size of Φ6nm is N6, 350<Φ6≤500, 1%≤N6 / N≤5%. Exemplarily, Φ6 can be 351, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500 or a range consisting of any two of the above values; N6 / N can be 1%, 2%, 3%, 4%, 5% or a range consisting of any two of the above values. When the ratio of the number of primary particles N6 of lithium manganese iron phosphate with a particle size Φ6 satisfying 350<Φ6≤500 to the total number of primary particles N of lithium manganese iron phosphate is within the scope of the present application, lithium manganese iron phosphate satisfies the above particle size distribution, and lithium manganese iron phosphate has a certain number of particles with larger particle sizes, which can further improve the processing performance of the positive electrode material, such as increasing the compaction density of the positive electrode material.
[0033] In one or more embodiments of the present application, the number of primary particles of lithium manganese iron phosphate with a particle size of Φ7nm is N7, Φ7>500, 0≤N7 / N≤5%. Exemplarily, Φ7 can be 501, 505, 510, 520, 530, 540, 550, 560, 570, 580, 590, 600 or a range consisting of any two of the above values; N7 / N can be 0, 1%, 2%, 3%, 4%, 5% or a range consisting of any two of the above values. When the ratio of the number of primary particles N7 of lithium manganese iron phosphate with a particle size Φ7 satisfying Φ7>500 to the total number of primary particles N of lithium manganese iron phosphate is within the scope of the present application, lithium manganese iron phosphate satisfies the above particle size distribution, and lithium manganese iron phosphate has a certain number of particles with larger particle sizes, which can further improve the processing performance of the positive electrode material, such as increasing the compaction density of the positive electrode material.
[0034] In one or more embodiments of the present application, the average particle size of lithium manganese iron phosphate is D nm, 50≤D≤200. Exemplarily, D can be 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200 or a range consisting of any two of the above values. The particle size distribution of lithium manganese iron phosphate will affect the average particle size of lithium manganese iron phosphate. By regulating the average particle size of lithium manganese iron phosphate within the scope of the present application, lithium manganese iron phosphate includes particles with smaller particle sizes, as well as particles with medium particle sizes and larger particle sizes. The particles with smaller particle sizes in lithium manganese iron phosphate can improve the kinetic properties of the positive electrode material, such as rate performance or low-temperature discharge performance, and effectively reduce the attenuation of the kinetic properties of the positive electrode material during the cycle. In addition, lithium manganese iron phosphate has a certain number of particles with medium particle sizes and larger particle sizes, which can improve the processing properties of the positive electrode material, such as increasing the compaction density of the positive electrode material.
[0035] In one or more embodiments of the present application, based on the mass of lithium iron manganese phosphate, the mass percentage of carbon in lithium iron manganese phosphate is Wc%, 1.0≤Wc≤2.5, preferably, 1.3≤Wc≤2.0; more preferably, 1.5≤Wc≤1.8. Exemplarily, Wc can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 or a range consisting of any two of the above values. By regulating the mass percentage of carbon in lithium iron manganese phosphate within the scope of the present application, the electronic conductivity of lithium iron manganese phosphate can be further improved, thereby further improving the kinetic performance and cycle performance of the positive electrode material.
[0036] In one or more embodiments of the present application, the specific surface area of lithium manganese iron phosphate is SSA m 2 / g, 12≤SSA≤35; preferably, 14≤SSA≤20. Exemplarily, SSA can be 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35 or a range consisting of any two of the above values. By regulating the specific surface area of lithium manganese iron phosphate within the scope of this application, lithium manganese iron phosphate has a suitable specific surface area, lithium manganese iron phosphate has a suitable particle size distribution, lithium manganese iron phosphate includes particles with smaller particle sizes, and also includes particles with medium particle sizes and larger particle sizes. The particles with smaller particle sizes in lithium manganese iron phosphate can improve the kinetic properties of the positive electrode material, such as rate performance or low-temperature discharge performance, and effectively reduce the attenuation of the kinetic properties of the positive electrode material during the cycle. In addition, lithium manganese iron phosphate has a certain number of particles with medium particle sizes and larger particle sizes, which can improve the processing performance of the positive electrode material, such as increasing the compaction density of the positive electrode material.
[0037] In one or more embodiments of the present application, the powder resistivity of lithium iron manganese phosphate is ρΩ·cm, 10≤ρ≤300, preferably, 10≤ρ≤100. Exemplarily, ρ can be 10, 30, 50, 70, 90, 100, 110, 130, 150, 170, 190, 200, 210, 230, 250, 270, 290, 300 or a range consisting of any two of the above values. By regulating the powder resistivity of lithium iron manganese phosphate within the scope of the present application, the powder resistivity of lithium iron manganese phosphate is small, the electronic conductivity of lithium iron manganese phosphate is good, and the kinetic performance and cycle performance of the positive electrode material can be further improved.
[0038] In one or more embodiments of the present application, the chemical formula of lithium manganese iron phosphate is Li x Mn y Fe 1-y-z M zPO4, 1.0≤x≤1.1, 0.5≤y≤0.8, 0≤z≤0.02, M includes at least one of Mg, Ti, Nb, V, Ni or Co. Illustratively, x can be 1.0, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, or a range consisting of any two of the above values; y can be 0.5, 0.53, 0.55, 0.57, 0.6, 0.63, 0.65, 0.67, 0.7, 0.73, 0.75, 0.77, 0.8, or a range consisting of any two of the above values; z can be 0, 0.003, 0.005, 0.007, 0.009, 0.01, 0.013, 0.015, 0.017, 0.019, 0.02, or a range consisting of any two of the above values. The above-mentioned lithium manganese iron phosphate is selected. The lithium manganese iron phosphate has a higher energy density. At the same time, the lithium manganese iron phosphate satisfies the above-mentioned particle size distribution. The lithium manganese iron phosphate includes particles with smaller particle sizes, as well as particles with medium particle sizes and larger particle sizes. The positive electrode material can be used in secondary batteries, which can make the secondary batteries have better processing performance, dynamic performance, cycle performance and higher energy density.
[0039] The present application has no particular restrictions on the preparation method of the positive electrode material. Exemplarily, the preparation method of the positive electrode material may include but is not limited to the following steps: adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of A first precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of The first precursor solution and the second precursor solution are mixed, and then spray granulation, sintering, cooling, and air flow pulverization are performed to obtain the positive electrode material. When glucose is added, glucose reacts with the precursor during the heating process, so that Mn 3+ / Fe 3+ Reduction to Mn 2+ / Fe 2+ , forming LiFeMnPO4; and adding glucose can also form a carbon coating layer to improve the electronic conductivity of the positive electrode material. The above-mentioned precursors refer to manganese source, iron source, lithium source, and phosphorus source. The positive electrode material includes lithium manganese iron phosphate.
[0040] Exemplarily, the preparation method of the positive electrode material may include but is not limited to the following steps: adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of A first precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A second precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of the first precursor solution, the second precursor solution and the third precursor solution are mixed, and then spray granulated, sintered, cooled, and air flow crushed to obtain a positive electrode material.
[0041] Exemplarily, the preparation method of the positive electrode material may include but is not limited to the following steps: adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of A first precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A second precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A third precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of the first precursor solution, the second precursor solution, the third precursor solution and the fourth precursor solution are mixed, and then spray granulated, sintered, cooled, and air flow crushed to obtain a positive electrode material.
[0042] Exemplarily, the preparation method of the positive electrode material may include but is not limited to the following steps: adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of A first precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A second precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A third precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A fourth precursor solution; adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution and the fifth precursor solution are mixed, and then spray granulated, sintered, cooled, and air flow crushed to obtain a positive electrode material.
[0043] Exemplarily, the preparation method of the positive electrode material may include but is not limited to the following steps: adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of A first precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A second precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A third precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A fourth precursor solution; adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of A fifth precursor solution; adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of the sixth precursor solution; the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution and the sixth precursor solution are mixed, and then spray granulated, sintered, cooled, and air flow crushed to obtain a positive electrode material.
[0044] Exemplarily, the preparation method of the positive electrode material may include but is not limited to the following steps: adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of A first precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A second precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A third precursor solution is prepared; a manganese source, an iron source, a lithium source, and a phosphorus source are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of A fourth precursor solution; adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of A fifth precursor solution; adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of A sixth precursor solution; adding a manganese source, an iron source, a lithium source, and a phosphorus source to water in a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of the seventh precursor solution; the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution, the sixth precursor solution and the seventh precursor solution are mixed, and then spray granulated, sintered, cooled, and air flow crushed to obtain a positive electrode material.
[0045] The present application has no particular restrictions on the manganese source, as long as the purpose of the present application can be achieved, for example, the manganese source may include but is not limited to Mn3O4. The present application has no particular restrictions on the iron source, as long as the purpose of the present application can be achieved, for example, the iron source may include but is not limited to FePO4. The present application has no particular restrictions on the lithium source, as long as the purpose of the present application can be achieved, for example, the lithium source may include but is not limited to Li2CO3. The present application has no particular restrictions on the phosphorus source, as long as the purpose of the present application can be achieved, for example, the phosphorus source may include but is not limited to LiH2PO4. The present application has no particular restrictions on the mass ratio of glucose to lithium manganese iron phosphate, as long as the purpose of the present application can be achieved, for example, the mass ratio of glucose to lithium manganese iron phosphate can be (0.1:1) to (0.25:1). The present application has no particular restrictions on the solid content of the intermediate solution, as long as the purpose of the present application can be achieved, for example, the solid content of the intermediate solution can be 20wt% to 35wt%. In the present application, the particle size in the first precursor solution or the second precursor solution can be regulated by regulating the grinding time of the mixed grinding. The present application has no particular limitation on the sintering temperature and sintering time, as long as the purpose of the present application can be achieved. For example, the sintering temperature can be 600° C. to 800° C.; the sintering time can be 6 h to 20 h.
[0046] The present application has no particular restrictions on the method for regulating the ratio of the number N1 of primary particles of lithium manganese iron phosphate with a particle size Φ1 satisfying 50<Φ1≤100 to the total number N of primary particles of lithium manganese iron phosphate, and the ratio of the number N2 of primary particles of lithium manganese iron phosphate with a particle size Φ2 satisfying 100<Φ2≤150 to the total number N of primary particles of lithium manganese iron phosphate, as long as the purpose of the present application can be achieved. For example, the ratio of the number N1 of primary particles of lithium manganese iron phosphate with a particle size Φ1 satisfying 50<Φ1≤100 to the total number N of primary particles of lithium manganese iron phosphate, and the ratio of the number N2 of primary particles of lithium manganese iron phosphate with a particle size Φ2 satisfying 100<Φ2≤150 to the total number N of primary particles of lithium manganese iron phosphate can be regulated by regulating the mass ratio of the mixture of the first precursor solution and the second precursor solution.
[0047] The present application has no particular restrictions on the method for regulating the ratio of the number N3 of primary particles of lithium manganese iron phosphate whose particle size Φ3 satisfies Φ3≤50 to the total number N of primary particles of lithium manganese iron phosphate, as long as the purpose of the present application can be achieved. For example, the ratio of the number N3 of primary particles of lithium manganese iron phosphate whose particle size Φ3 satisfies Φ3≤50 to the total number N of primary particles of lithium manganese iron phosphate can be regulated by regulating the mass ratio of the mixture of the first precursor solution, the second precursor solution, and the third precursor solution.
[0048] The present application has no particular restrictions on the method for regulating the ratio of the number N4 of primary particles of lithium manganese iron phosphate whose particle size Φ4 satisfies 150<Φ4≤250 to the total number N of primary particles of lithium manganese iron phosphate, as long as the purpose of the present application can be achieved. For example, the ratio of the number N4 of primary particles of lithium manganese iron phosphate whose particle size Φ4 satisfies 150<Φ4≤250 to the total number N of primary particles of lithium manganese iron phosphate can be regulated by regulating the mass ratio of the mixture of the first precursor solution, the second precursor solution, the third precursor solution and the fourth precursor solution.
[0049] The present application has no particular restrictions on the method for regulating the ratio of the number N5 of primary particles of lithium manganese iron phosphate whose particle size Φ5 satisfies 250<Φ5≤350 to the total number N of primary particles of lithium manganese iron phosphate, as long as the purpose of the present application can be achieved. For example, the ratio of the number N5 of primary particles of lithium manganese iron phosphate whose particle size Φ5 satisfies 250<Φ5≤350 to the total number N of primary particles of lithium manganese iron phosphate can be regulated by regulating the mass ratio of the mixture of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution and the fifth precursor solution.
[0050] The present application has no particular restrictions on the method for regulating the ratio of the number N6 of primary particles of lithium manganese iron phosphate whose particle size Φ6 satisfies 350<Φ6≤500 to the total number N of primary particles of lithium manganese iron phosphate, as long as the purpose of the present application can be achieved. For example, the ratio of the number N6 of primary particles of lithium manganese iron phosphate whose particle size Φ6 satisfies 350<Φ6≤500 to the total number N of primary particles of lithium manganese iron phosphate can be regulated by regulating the mass ratio of the mixture of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution and the sixth precursor solution.
[0051] The present application has no particular restrictions on the method for regulating the ratio of the number N7 of primary particles of lithium manganese iron phosphate with a particle size Φ7 satisfying Φ7>500 to the total number N of primary particles of lithium manganese iron phosphate, as long as the purpose of the present application can be achieved. For example, the ratio of the number N7 of primary particles of lithium manganese iron phosphate with a particle size Φ7 satisfying Φ7>500 to the total number N of primary particles of lithium manganese iron phosphate can be regulated by regulating the mass ratio of the mixture of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution, the sixth precursor solution and the seventh precursor solution.
[0052] The present application has no particular restrictions on the method for regulating the average particle size of lithium manganese iron phosphate, as long as the purpose of the present application can be achieved. For example, the average particle size of lithium manganese iron phosphate can be regulated by regulating the mass ratio of the first precursor solution and the second precursor solution.
[0053] The present application has no particular restrictions on the method for regulating the mass percentage of carbon in lithium iron manganese phosphate, as long as the purpose of the present application can be achieved. For example, the mass percentage of carbon in lithium iron manganese phosphate can be regulated by regulating the mass ratio of glucose to lithium iron manganese phosphate.
[0054] In the present application, it is understood that the positive electrode material prepared by adding a doping element precursor to the reactant includes lithium iron manganese phosphate, and the lithium iron manganese phosphate contains a doping element M. Exemplarily, the preparation method of the positive electrode material may include but is not limited to the following steps: adding a manganese source, an iron source, a lithium source, a phosphorus source, and a doping element precursor to water according to a certain molar ratio, adding glucose to obtain an intermediate solution, mixing and grinding the intermediate solution to obtain particles with a particle size of A first precursor solution is prepared; a manganese source, an iron source, a lithium source, a phosphorus source, and a doping element precursor are added to water in a certain molar ratio, and glucose is added to obtain an intermediate solution, and the intermediate solution is mixed and ground to obtain particles with a particle size of the first precursor solution and the second precursor solution are mixed, and then spray granulation, sintering, cooling, and air flow pulverization to obtain a positive electrode material.
[0055] The present application has no particular restrictions on the doping element precursor, as long as the purpose of the present application can be achieved. For example, the doping element precursor may include but is not limited to the oxide, hydroxide or sulfate of the doping element. For example, the oxide of the doping element may include but is not limited to MgO, TiO2, Nb2O5, V2O5, NiO or CoO; the hydroxide of the doping element may include but is not limited to Mg(OH)2; the sulfate of the doping element may include but is not limited to MgSO4 or CoSO4.
[0056] In the present application, Dv50 means the particle size at which the volume accumulation is 50% from the smallest particle size in the volume-based particle size distribution of the material.
[0057] The second aspect of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode material layer disposed on at least one surface of the positive electrode collector, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes the positive electrode material in any of the aforementioned embodiments. Therefore, applying the positive electrode plate to a secondary battery can enable the secondary battery to have better processing performance, dynamic performance and cycle performance. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode collector along its own thickness direction, or on two surfaces of the positive electrode collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the positive electrode collector or a partial area of the positive electrode collector. There is no special limitation in this application, as long as the purpose of this application can be achieved.
[0058] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0059] The positive electrode material layer of the present application also includes a positive electrode conductor and a positive electrode binder. The present application has no particular restrictions on the positive electrode conductor and the positive electrode binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor may include but is not limited to at least one of conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. The above-mentioned conductive carbon black may include but is not limited to at least one of Super P, acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The positive electrode binder may include at least one of polyacrylate, polyimide, polyamide, polyamideimide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene butadiene rubber, SBR), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, lithium carboxymethyl cellulose, lithium polyacrylate, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. The present application does not particularly limit the mass ratio of the positive electrode active material, the positive electrode conductor, and the positive electrode binder in the positive electrode material layer, and those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved.
[0060] The present application has no particular limitation on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode current collector is 6 μm to 25 μm. The present application has no particular limitation on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided positive electrode material layer is 25 μm to 250 μm.
[0061] Optionally, the positive electrode plate may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above-mentioned positive electrode conductive agent and the above-mentioned positive electrode binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0062] The third aspect of the present application provides a secondary battery, the secondary battery comprising the positive electrode sheet in any of the above embodiments. Therefore, the secondary battery provided by the present application has good processing performance, dynamic performance and cycle performance.
[0063] In the present application, the secondary battery also includes a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0064] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.
[0065] The negative electrode material layer of the present application includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO x (0.5<x<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12 , Li-Al alloy or metallic lithium, etc. The negative electrode material layer of the present application also includes a negative electrode binder and a negative electrode conductive agent. The present application has no special restrictions on the negative electrode binder and the negative electrode conductive agent in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the negative electrode binder can be at least one of the above-mentioned positive electrode binders, and the negative electrode conductive agent can be at least one of the above-mentioned positive electrode conductive agents. The present application has no special restrictions on the mass ratio of the negative electrode active material, the negative electrode binder, and the negative electrode conductive agent in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0066] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 4 μm to 20 μm. The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided negative electrode material layer is 30 μm to 250 μm.
[0067] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above-mentioned negative electrode conductive agent and the above-mentioned negative electrode binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0068] In the present application, the secondary battery also includes an electrolyte. The electrolyte includes a lithium salt. The present application has no particular restrictions on the type of lithium salt, and lithium salts known in the art can be used. For example, the lithium salt may include but is not limited to lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiN(CF3SO2)2, LiTFSI), lithium bis(fluorosulfonyl)imide (Li(N(SO2F)2), LiFSI), lithium difluorophosphate (LiPO2F2), lithium bis(oxalate borate) (LiB(C2O4)2, LiBOB) or lithium difluorooxalate borate (LiBF2(C2O4), LiDFOB). The present application has no particular restrictions on the mass percentage of lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. The electrolyte also includes a non-aqueous organic solvent. The present application has no particular restrictions on the non-aqueous organic solvent, as long as the purpose of the present application can be achieved. For example, the non-aqueous organic solvent may contain at least one of a carbonate compound, a carboxylate compound, an ether compound or other organic solvents. The above-mentioned carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), vinylene carbonate, propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned fluorinated carbonate compound may include but is not limited to fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate or propyl propionate. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include, but are not limited to, at least one of 1,3-propanesultone, dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate ester.The present application has no particular limitation on the mass percentage of the non-aqueous organic solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0069] In the present application, the secondary battery also includes a diaphragm. The diaphragm is used to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of diaphragm may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0070] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a diaphragm binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned diaphragm binder, for example, it may be at least one of the aforementioned negative electrode binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or vinylidene fluoride-hexafluoropropylene copolymer.
[0071] The secondary battery of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.
[0072] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.
[0073] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no special restrictions. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the pre-lithiated negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the positive electrode sheet, the separator and the pre-lithiated negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection components, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.
[0074] The fourth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good processing performance, dynamic performance and cycle performance.
[0075] The present application does not particularly limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0076] Example
[0077] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0078] Test methods and equipment:
[0079] Scanning electron microscope test:
[0080] The positive electrode material was characterized using a Philips XL-30 field emission scanning electron microscope (SEM). The test conditions were: acceleration voltage of 10 kV, grating of 10 spot, working distance of 10 mm, magnification of 10000 times, and a scanning electron microscope image of the positive electrode material was obtained. In the scanning electron microscope image of the positive electrode material with a magnification of 10000 times and a range of 10μm×8μm, a positive electrode material with a total number of primary particles of N is selected, and the number of primary particles of the positive electrode material whose particle size Φ1 satisfies 50<Φ1≤100 is counted N1, the number of primary particles of the positive electrode material whose particle size Φ2 satisfies 100<Φ2≤150 is counted N2, the number of primary particles of the positive electrode material whose particle size Φ3 satisfies Φ3≤50 is counted N3, the number of primary particles of the positive electrode material whose particle size Φ4 satisfies 150<Φ4≤250 is counted N4, the number of primary particles of the positive electrode material whose particle size Φ5 satisfies 250<Φ5≤350 is counted N5, the number of primary particles of the positive electrode material whose particle size Φ6 satisfies 350<Φ6≤500 is counted N6, and the number of primary particles of the positive electrode material whose particle size Φ7 satisfies Φ7>500 is counted N7.
[0081] The calculation method of the average particle size of the positive electrode material is as follows: In the scanning electron microscope image of the positive electrode material with a magnification of 10,000 times and a range of 10μm×8μm, a positive electrode material with a total number of primary particles of N is selected, and the sum of the particle sizes of N positive electrode materials divided by N is the average particle size of the positive electrode material.
[0082] Carbon mass percentage test:
[0083] For the positive electrode material powder, a carbon-sulfur analyzer (model: DK-606) is directly used to test the mass percentage of carbon element in the positive electrode material powder.
[0084] For the prepared positive electrode sheets or the positive electrode sheets removed from the lithium-ion battery, the sheets in the coated area were cut into sheets, ultrasonically vibrated in an N-methylpyrrolidone (NMP) bath at 100°C for 48 hours, the current collector was removed, the remaining material was ground for 1 hour, washed and filtered 3 times to remove the colloid, and the remaining solid material was dried at 100°C for 8 hours, and the obtained powder was taken to test the mass percentage of carbon element using a carbon-sulfur analyzer (model DK-606).
[0085] Specific surface area test:
[0086] In accordance with the national standard "Determination of the specific surface area of solid substances by gas adsorption BET method" (GB / T 19587-2017), the specific surface area of the positive electrode material was tested by nitrogen adsorption method using a specific surface area analyzer (model TristarⅡ3020M).
[0087] Powder resistivity test:
[0088] The resistivity tester (Suzhou Jingge Electronics, model ST-2255A) was used to test the powder resistivity of the positive electrode material. 5g of positive electrode material powder was taken and pressed into tablets using an electronic press. The electronic press was pressed to 5000kg and maintained for 20s to obtain a positive electrode material sample. The positive electrode material sample was placed between the electrodes of the resistivity tester for testing, and the resistance r of the positive electrode material sample was measured. And calculated according to the following formula:
[0089] ρ = r × s / l;
[0090] Wherein, ρ is the powder resistivity; r is the measured resistance of the positive electrode material sample (in Ω); l is the thickness of the positive electrode material sample (in cm); s is the bottom area of the positive electrode material sample (in cm 2 ).
[0091] Compacted density test of positive electrode material:
[0092] Weigh 1.0g of the positive electrode material sample and place it in the test mold (CARVER#3619 (13mm)), and then place the positive electrode material sample in the test equipment. The test equipment is Sansi Zongheng UTM7305, the test pressure is 3T, the pressurization displacement rate is 10mm / min, the pressure increase holding time is 30s, the pressure relief displacement rate is 30mm / min, and the pressure relief holding time is 10s.
[0093] The calculation formula for compacted density is: compacted density = sample mass / (sample force area × sample thickness).
[0094] DC resistance (DCR) test:
[0095] At 25°C, the lithium-ion battery is charged to 4.3V at a constant current of 0.1C, and then charged to 0.025C at a constant voltage of 4.3V, and allowed to stand for 10 minutes; then discharged at a constant current of 0.1C for 5 hours (at this time the lithium-ion battery is at a 50% state of charge); then discharged at a constant current of 1C for 1 second; the voltage before the above 1C constant current discharge is V0, the voltage after the above 1C constant current discharge is V1, the current of the above 1C constant current discharge is A, and the DC impedance R corresponding to the 50% state of charge (SOC) of the lithium-ion battery is calculated to be (V0-V1) / A.
[0096] The smaller the DC impedance corresponding to 50% state of charge (SOC) of the lithium-ion battery, the better the dynamic performance of the lithium-ion battery.
[0097] Low temperature discharge performance test:
[0098] At 25°C, the lithium-ion battery was charged to 4.3V at a constant current of 0.3C, charged to 0.025C at a constant voltage at 4.3V, left to stand for 10 minutes, and then discharged to 2.5V at a constant current of 0.3C, and the above discharge capacity was recorded as C0; then, the lithium-ion battery was charged to 4.3V at a constant current of 0.3C, charged to 0.025C at a constant voltage at 4.3V, and then the lithium-ion battery was placed in a -20°C constant temperature box for 4 hours, and then discharged to 2.5V at a constant current of 0.3C, and the above discharge capacity was recorded as C1.
[0099] -20℃ capacity retention rate (%) = C1 / C0×100%.
[0100] Cycle performance test:
[0101] At 45°C, the lithium-ion battery is charged and discharged for the first time. The specific steps are: charge the lithium-ion battery to 4.3V at a constant current of 0.5C, charge to 0.025C at a constant voltage of 4.3V, let it stand for 10 minutes, and then discharge to 2.5V at a constant current of 0.5C. The discharge capacity of the lithium-ion battery is measured to be C2. The ratio of the discharge energy to the discharge capacity in the above discharge process is the initial equalizing pressure. This is a charge and discharge cycle process. According to the above steps, 500 cycles (cls) of charge and discharge cycles are performed. The discharge capacity of the lithium-ion battery in the 500th cycle is measured to be C3. The ratio of the discharge energy to the discharge capacity in the 500th cycle of discharge process is the equalizing pressure of the 500th cycle. The equalizing pressure drop = the equalizing pressure of the 500th cycle - the initial equalizing pressure, where the unit of discharge energy is mWh and the unit of discharge capacity is Ah.
[0102] 500-cycle capacity retention rate (%) = C3 / C2×100%.
[0103] The higher the 500-cycle capacity retention rate and the smaller the average voltage drop, the better the stability of the positive electrode material and the better the cycle performance of the lithium-ion battery.
[0104] Example 1-1
[0105] <Preparation of positive electrode material>
[0106] Manganese source Mn3O4, iron source FePO4, lithium source Li2CO3, phosphorus source LiH2PO4, and MgO are designed according to the corresponding molar ratio of this embodiment. 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The first precursor solution is 300 nm. The manganese source Mn3O4, the iron source FePO4, the lithium source Li2CO3, the phosphorus source LiH2PO4, and the MgO are designed according to the corresponding molar ratio of this embodiment. 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The second precursor solution is 350nm. The manganese source Mn3O4, the iron source FePO4, the lithium source Li2CO3, the phosphorus source LiH2PO4, and the MgO are designed according to the corresponding molar ratio of this embodiment. 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The fourth precursor solution is 500 nm. The manganese source Mn3O4, the iron source FePO4, the lithium source Li2CO3, the phosphorus source LiH2PO4, and the MgO are designed according to the corresponding molar ratio of this embodiment. 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The fifth precursor solution is 800 nm. The manganese source Mn3O4, the iron source FePO4, the lithium source Li2CO3, the phosphorus source LiH2PO4, and the MgO are designed according to the corresponding molar ratio of this embodiment. 1.05 Mn 0.5 Fe 0.49 Mg0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The first precursor solution, the second precursor solution, the fourth precursor solution, the fifth precursor solution and the sixth precursor solution are mixed in a mass ratio of 1.53:8.52:39.54:39.25:11.16, and then spray granulated and sintered in a nitrogen atmosphere at a sintering temperature of 700°C for 8 hours, and then cooled and pulverized by air flow to obtain a positive electrode material. The positive electrode material includes lithium manganese iron phosphate, and the chemical formula of lithium manganese iron phosphate is Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 PO4. The precursor for doping Mg element is MgO.
[0107] <Preparation of positive electrode sheet>
[0108] After mixing the above-mentioned positive electrode material, positive electrode conductive agent Super P, and positive electrode binder polyvinylidene fluoride (PVDF) in a weight ratio of 96.7:0.8:2.5, add N-methylpyrrolidone (NMP) as a solvent, stir and mix evenly to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 60wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 90°C to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 90°C for 1h, and then after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 74mm×867mm is obtained. Among them, the coating weight of the positive electrode material layer is 180g / m 2 The compaction density of the cold pressing process is 2.3g / cm 3 .
[0109] <Preparation of negative electrode sheet>
[0110] After mixing the negative electrode active material artificial graphite, the negative electrode conductive agent Super P, and the negative electrode binder lithium polyacrylate (PAA-Li) in a weight ratio of 97.3:1.5:1.2, deionized water is added as a solvent, and the mixture is stirred to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 50wt%; the negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 110°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. Dry under vacuum conditions at 110°C for 1h, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 78mm×875mm is obtained. Among them, the particle size Dv50 of the negative electrode active material artificial graphite is 14μm; the coating weight of the negative electrode material layer is 84g / m 2 The compaction density of the cold pressing process is 1.6g / cm 3 .
[0111] <Preparation of Electrolyte>
[0112] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed at a mass ratio of EC:EMC:DEC=30:50:20 to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) was added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 was 12.5%, and the remainder was the base solvent.
[0113] <Preparation of Separator>
[0114] The membrane binder PVDF and inorganic particle alumina are mixed in a mass ratio of 1:2, NMP is added as a solvent, and an inorganic layer slurry with a solid content of 12wt% is prepared, and stirred evenly. The inorganic layer slurry is evenly coated on one surface of a polyethylene substrate with a thickness of 15μm, and dried at 85℃ for 4h to obtain a single-sided inorganic layer-coated membrane with a coating thickness of 3μm. Then PVDF is added to the NMP solvent and stirred evenly to prepare a polymer layer slurry with a solid content of 25wt%, and then the polymer layer slurry is evenly coated on the surface of the inorganic layer. The coating weight of the coated polymer layer slurry is 1.5mg / 1540.25mm 2 , and then dried at 85°C for 4 hours, and finally the polymer layer slurry was evenly coated on the other surface of the polyethylene substrate, and the coating weight of the polymer layer slurry was 1.5 mg / 1540.25 mm 2 , and then dried at 85°C for 4 hours to obtain a diaphragm coated with an inorganic layer and a polymer layer on one side and only a polymer layer on the other side.
[0115] <Preparation of lithium-ion batteries>
[0116] The prepared positive electrode sheet, separator, negative electrode sheet and separator are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound. After welding the pole ear, the electrode assembly is placed in an aluminum plastic film packaging bag, placed in a vacuum oven at 85°C for 12 hours to remove moisture, and the electrolyte is injected. After vacuum packaging, standing, formation (charging to 3.3V at a constant current of 0.02C, and then charging to 4.3V at a constant current of 0.3C), degassing, trimming, and capacity processing steps, a lithium-ion battery is obtained.
[0117] Example 1-2
[0118] Except for preparing the positive electrode material according to the following method, the rest is the same as Example 1-1.
[0119] <Preparation of positive electrode material>
[0120] Manganese source Mn3O4, iron source FePO4, lithium source Li2CO3, phosphorus source LiH2PO4, and MgO are designed according to the corresponding molar ratio of this embodiment. 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The first precursor solution is 300 nm. The manganese source Mn3O4, the iron source FePO4, the lithium source Li2CO3, the phosphorus source LiH2PO4, and the MgO are designed according to the corresponding molar ratio of this embodiment. 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The second precursor solution is 350nm. The manganese source Mn3O4, the iron source FePO4, the lithium source Li2CO3, the phosphorus source LiH2PO4, and the MgO are designed according to the corresponding molar ratio of this embodiment. 1.05 Mn 0.5 Fe 0.49Mg 0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The third precursor solution is 250 nm. The manganese source Mn3O4, the iron source FePO4, the lithium source Li2CO3, the phosphorus source LiH2PO4, and the MgO are designed according to the corresponding molar ratio of this embodiment. 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The fourth precursor solution is 500 nm. The manganese source Mn3O4, the iron source FePO4, the lithium source Li2CO3, the phosphorus source LiH2PO4, and the MgO are designed according to the corresponding molar ratio of this embodiment. 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The fifth precursor solution is 800 nm. The manganese source Mn3O4, the iron source FePO4, the lithium source Li2CO3, the phosphorus source LiH2PO4, and the MgO are designed according to the corresponding molar ratio of this embodiment. 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The sixth precursor solution is 1000 nm. The manganese source Mn3O4, the iron source FePO4, the lithium source Li2CO3, the phosphorus source LiH2PO4, and the MgO are designed with the corresponding molar ratio in this embodiment. 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The molar ratio of PO4 is added to water, glucose is added, glucose and Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 The mass ratio of PO4 is 0.16:1, and an intermediate solution is obtained. The solid content of the intermediate solution is 30wt%. The intermediate solution is mixed and ground to obtain a particle size of The first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution, the sixth precursor solution and the seventh precursor solution are mixed in a mass ratio of 0.24:1.66:0.01:18.10:22.91:21.72:35.36, and then spray granulated and sintered in a nitrogen atmosphere at a sintering temperature of 700°C and a sintering time of 8 hours. Then cooled and pulverized by air flow to obtain the positive electrode material. The positive electrode material includes lithium manganese iron phosphate, and the chemical formula of lithium manganese iron phosphate is Li 1.05 Mn 0.5 Fe 0.49 Mg 0.01 PO4. The precursor for doping Mg element is MgO.
[0121] Examples 1-3
[0122] The invention is the same as Example 1-2 except that the mass ratio of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution, the sixth precursor solution and the seventh precursor solution is adjusted so that N1 / N, N2 / N, N3 / N, N4 / N, N5 / N, N6 / N and N7 / N are as shown in Table 1.
[0123] Example 1-4 to Example 1-8
[0124] The invention is the same as Example 1-1 except that the mass ratio of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution and the sixth precursor solution is adjusted so that N1 / N, N2 / N, N3 / N, N4 / N, N5 / N and N6 / N are as shown in Table 1.
[0125] Example 1-9 to Example 1-11
[0126] The invention is the same as Example 1-2 except that the mass ratio of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution, the sixth precursor solution and the seventh precursor solution is adjusted so that N1 / N, N2 / N, N3 / N, N4 / N, N5 / N, N6 / N and N7 / N are as shown in Table 1.
[0127] Example 1-12 to Example 1-17
[0128] The invention is the same as Example 1-1 except that the mass ratio of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution and the sixth precursor solution is adjusted so that N1 / N, N2 / N, N3 / N, N4 / N, N5 / N and N6 / N are as shown in Table 1.
[0129] Example 1-18 to Example 1-20
[0130] The invention is the same as Example 1-2 except that the mass ratio of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution, the sixth precursor solution and the seventh precursor solution is adjusted so that N1 / N, N2 / N, N3 / N, N4 / N, N5 / N, N6 / N and N7 / N are as shown in Table 1.
[0131] Embodiment 1-21
[0132] The invention is the same as Example 1-1 except that the mass ratio of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution and the sixth precursor solution is adjusted so that N1 / N, N2 / N, N3 / N, N4 / N, N5 / N and N6 / N are as shown in Table 1.
[0133] Examples 1-22
[0134] The invention is the same as Example 1-2 except that the mass ratio of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution, the sixth precursor solution and the seventh precursor solution is adjusted so that N1 / N, N2 / N, N3 / N, N4 / N, N5 / N, N6 / N and N7 / N are as shown in Table 1.
[0135] Example 2-1 to Example 2-6
[0136] Except for adjusting the mass ratio of glucose to lithium iron manganese phosphate so that the mass percentage of carbon element in lithium iron manganese phosphate is as shown in Table 3, the rest is the same as Example 1-1.
[0137] Example 2-7 to Example 2-8
[0138] Except that no doping element precursor is added in <Preparation of Positive Electrode Material> and the molar ratio of manganese source, iron source, lithium source and phosphorus source is adjusted so that the chemical formula of lithium manganese iron phosphate is as shown in Table 3, the rest is the same as Example 1-1.
[0139] Embodiment 2-9
[0140] Except that the molar ratio of the manganese source, iron source, lithium source, phosphorus source and MgO is adjusted in <Preparation of Positive Electrode Material> so that the chemical formula of lithium manganese iron phosphate is as shown in Table 3, the rest is the same as Example 1-1.
[0141] Embodiment 2-10
[0142] Except that TiO2 is used as the doping element precursor in <Preparation of Positive Electrode Material> and the molar ratio of the manganese source, iron source, lithium source, phosphorus source and doping element precursor is adjusted so that the chemical formula of lithium manganese iron phosphate is as shown in Table 3, the rest is the same as Example 1-1.
[0143] Example 2-11
[0144] Except that Nb2O5 is used as the doping element precursor in <Preparation of Positive Electrode Material> and the molar ratio of the manganese source, iron source, lithium source, phosphorus source and doping element precursor is adjusted so that the chemical formula of lithium manganese iron phosphate is as shown in Table 3, the rest is the same as Example 1-1.
[0145] Comparative Examples 1 to 4
[0146] The present invention is the same as Example 1-1 except that the mass ratio of the first precursor solution, the second precursor solution, the third precursor solution, the fourth precursor solution, the fifth precursor solution, the sixth precursor solution and the seventh precursor solution is adjusted so that N1 / N, N2 / N, N3 / N, N4 / N, N5 / N, N6 / N and N7 / N are as shown in Table 1.
[0147] The preparation parameters and electrical performance parameters of each embodiment and comparative example are shown in Tables 1 to 3.
[0148]
[0149]
[0150] Table 2
[0151]
[0152] Note: (1) In Table 2, in Comparative Example 2, the "DC impedance R corresponding to 50% state of charge (SOC) of lithium-ion battery" is "unable to be processed", the "-20°C capacity retention rate" is "unable to be processed", the "500-cycle capacity retention rate" is "unable to be processed", and the "average voltage drop" is "unable to be processed", indicating that the lithium-ion battery cannot be processed and the lithium-ion battery has no corresponding performance.
[0153] It can be seen from Examples 1-1 to 1-22 and Comparative Examples 1 to 4 that when the positive electrode material includes lithium iron manganese phosphate, when the ratio of the number N1 of primary particles of lithium iron manganese phosphate with a particle size Φ1 satisfying 50<Φ1≤100 to the total number N of primary particles of lithium iron manganese phosphate, and the ratio of the number N2 of primary particles of lithium iron manganese phosphate with a particle size Φ2 satisfying 100<Φ2≤150 to the total number N of primary particles of lithium iron manganese phosphate are within the scope of the present application, the positive electrode material has a higher compaction density, and the prepared lithium-ion battery has a lower DC impedance, a higher -20°C capacity retention rate, a higher 500-cycle capacity retention rate, and a lower average voltage drop, indicating that the processing performance, kinetic performance and cycle performance of the positive electrode material can be improved. In Comparative Examples 1 to 4, the ratio of the number N1 of primary particles of lithium iron manganese phosphate whose particle size Φ1 satisfies 50<Φ1≤100 to the total number N of primary particles of lithium iron manganese phosphate, and / or the ratio of the number N2 of primary particles of lithium iron manganese phosphate whose particle size Φ2 satisfies 100<Φ2≤150 to the total number N of primary particles of lithium iron manganese phosphate are not within the scope of the present application, the positive electrode material has a lower compaction density, and the prepared lithium-ion battery has a higher DC impedance, a lower -20°C capacity retention rate, a lower 500-cycle capacity retention rate, and a higher average voltage drop, indicating that the processing performance, kinetic performance and cycle performance of the positive electrode material are poor.
[0154] The average particle size of lithium iron manganese phosphate usually affects the kinetic performance and cycle performance of lithium-ion batteries. From Examples 1-1 to 1-22, it can be seen that the average particle size of lithium iron manganese phosphate is within the scope of this application, and the prepared lithium-ion battery has a lower DC impedance, a higher -20°C capacity retention rate, a higher 500-cycle capacity retention rate, and a lower average voltage drop, indicating that the processing performance, kinetic performance, and cycle performance of the positive electrode material can be improved.
[0155] The specific surface area of lithium iron manganese phosphate usually affects the kinetic performance and cycle performance of lithium ion batteries. It can be seen from Examples 1-1 to 1-22 that the specific surface area of lithium iron manganese phosphate is within the scope of this application, and the prepared lithium ion battery has a lower DC impedance, a higher -20°C capacity retention rate, a higher 500-cycle capacity retention rate, and a lower average voltage drop, indicating that the processing performance, kinetic performance, and cycle performance of the positive electrode material can be improved.
[0156] The powder resistivity of lithium iron manganese phosphate usually affects the kinetic performance and cycle performance of lithium ion batteries. It can be seen from Examples 1-1 to 1-22 that the powder resistivity of lithium iron manganese phosphate is within the scope of this application, and the prepared lithium ion battery has a lower DC impedance, a higher -20°C capacity retention rate, a higher 500-cycle capacity retention rate, and a lower average voltage drop, indicating that the processing performance, kinetic performance, and cycle performance of the positive electrode material can be improved.
[0157] Depend on Figure 1 It can be seen that the morphology of the positive electrode material of Example 1-1 is granular.
[0158] Table 3
[0159]
[0160] The mass percentage of carbon in lithium iron manganese phosphate usually affects the kinetic performance and cycle performance of lithium ion batteries. It can be seen from Examples 1-1, 2-1 to 2-6 that the mass percentage of carbon in lithium iron manganese phosphate is within the scope of this application, and the prepared lithium ion battery has a lower DC impedance, a higher -20°C capacity retention rate, a higher 500-cycle capacity retention rate, and a lower average voltage drop, indicating that the processing performance, kinetic performance, and cycle performance of the positive electrode material can be improved.
[0161] It can be seen from Example 1-1 and Example 2-7 to Example 2-11 that the chemical formula of lithium manganese iron phosphate is within the scope of the present application, and the prepared lithium-ion battery has lower DC impedance, higher -20°C capacity retention rate, higher 500-cycle capacity retention rate, and lower average voltage drop, indicating that the processing performance, kinetic performance, and cycle performance of the positive electrode material can be improved.
[0162] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0163] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0164] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A positive electrode material, comprising lithium manganese iron phosphate, characterized in that: In the scanning electron microscope image of the lithium manganese iron phosphate with a magnification of 10000 times and within a range of 10 μm×8 μm, the total number of primary particles of the lithium manganese iron phosphate is N, the number of primary particles of the lithium manganese iron phosphate with a particle size of Φ1 nm is N1, and the number of primary particles of the lithium manganese iron phosphate with a particle size of Φ2 nm is N2, and N≥200; 50<Φ1≤100, 10%≤N1 / N≤30%; 100<Φ2≤150, 15%≤N2 / N≤35%.
2. The positive electrode material according to claim 1, characterized in that The number of primary particles of the lithium manganese iron phosphate having a particle size of Φ3 nm is N3, Φ3≤50, 0≤N3 / N≤10%.
3. The positive electrode material according to claim 1, characterized in that The number of primary particles of the lithium manganese iron phosphate having a particle size of Φ4 nm is N4, 150<Φ4≤250, 20%≤N4 / N≤40%.
4. The positive electrode material according to claim 1, characterized in that The number of primary particles of the lithium manganese iron phosphate having a particle size of Φ5 nm is N5, 250<Φ5≤350, 5%≤N5 / N≤15%.
5. The positive electrode material according to claim 1, characterized in that The number of primary particles of the lithium manganese iron phosphate having a particle size of Φ6 nm is N6, 350<Φ6≤500, 1%≤N6 / N≤5%.
6. The positive electrode material according to claim 1, characterized in that The number of primary particles of the lithium manganese iron phosphate having a particle size of Φ7 nm is N7, Φ7>500, 0≤N7 / N≤5%.
7. The positive electrode material according to any one of claims 1 to 6, characterized in that The average particle size of the lithium manganese iron phosphate is D nm, 50≤D≤200.
8. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) Based on the mass of the lithium manganese iron phosphate, the mass percentage of carbon element in the lithium manganese iron phosphate is Wc%, 1.0≤Wc≤2.5; (2) The specific surface area of the lithium iron manganese phosphate is SSAm 2 / g, 12≤SSA≤35; (3) The powder resistivity of the lithium manganese iron phosphate is ρΩ·cm, 10≤ρ≤300.
9. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) Based on the mass of the lithium manganese iron phosphate, the mass percentage of carbon element in the lithium manganese iron phosphate is Wc%, and 1.3≤Wc≤2.0; (2) The specific surface area of the lithium iron manganese phosphate is SSAm 2 / g, 14≤SSA≤20; (3) The powder resistivity of the lithium manganese iron phosphate is ρΩ·cm, 10≤ρ≤100.
10. The positive electrode material according to claim 1, characterized in that Based on the mass of the lithium manganese iron phosphate, the mass percentage of carbon element in the lithium manganese iron phosphate is Wc%, and 1.5≤Wc≤1.
8.
11. The positive electrode material according to claim 1, characterized in that The chemical formula of the lithium manganese iron phosphate is Li x Mn y Fe 1-y-z M z PO4, 1.0≤x≤1.1, 0.5≤y≤0.8, 0≤z≤0.02, M includes at least one of Mg, Ti, Nb, V, Ni or Co. 12 . A positive electrode plate, comprising a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode material layer comprises the positive electrode material according to claim 1 . 13 . A secondary battery, comprising the positive electrode sheet according to claim 12 . 14 . An electronic device comprising the secondary battery according to claim 13 .
Citation Information
Patent Citations
Lithium iron manganese phosphate compound, preparing method thereof, and lithium ion battery positive electrode
CN112436120A
Positive electrode material, positive electrode slurry, positive electrode plate and battery
CN114204015A
Positive electrode material, positive electrode slurry, positive electrode plate and battery
CN114204016A
Coated modified lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN117954591A
Positive electrode active material, positive electrode, battery, and device
CN118231653A
Cited By
Positive electrode material, positive electrode sheet, secondary battery and electronic device
WO2026098070A1
Lithium secondary battery and electric device
WO2026200175A1